137k views
5 votes
How to solve

-3(m-2)=-9

m= ?

1 Answer

5 votes

9514 1404 393

Answer:

m = 5

Explanation:

Recognize that the number on the right has -3 as a factor. Divide both sides of the equation by -3.

m -2 = 3

Add 2 to both sides of the equation:

m = 5

_____

Additional comment

Perhaps the conventional approach is to eliminate parentheses, then solve the resulting 2-step linear equation.

-3m +6 = -9

-3m = -15 . . . . . . subtract 6 (step 1)

m = 5 . . . . . . . . . divide by the coefficient of m (step 2)

User Joe Crawley
by
5.2k points